Landfill leachate biological treatment: perspective for the aerobic granular sludge technology - Silva, Vicente Elício Porfiro Sales Gonçalves da (2022)
Landfill leachates are high-strength complex mixtures containing dissolved organic matter, ammonia, heavy metals, and sulfur species, among others. The problem of leachate treatment has subsisted for some time, but an efficient and cost-effective universal solution capable of ensuring environmental resources protection has not been found. Aerobic granular sludge (AGS) has been considered a promising technology for biological wastewater treatment in recent years. Granules’ layered structure, with an aerobic outer layer and an anaerobic/anoxic core, enables the presence of diverse microbial populations without the need for support media, allowing simultaneous removal of different pollutants in a single unit. Besides, its strong and compact arrangement provides higher tolerance to toxic pollutants and the ability to withstand large load fluctuations. Furthermore, its good that settling properties allow high biomass retention and better sludge separation. Nevertheless, AGS-related research has focused on carbon-nitrogen-phosphorus removal, mainly from sanitary sewage. This review aims to summarize and analyze the main findings and problems reported in the literature regarding AGS application to landfill leachate treatment and identify the knowledge gaps for future applications.